Observational study of scalpel versus electrocautery for subcutaneous incision in elective gynaecological surgeries - Patil, Vaibhav B.; Mule, Vidya D.; Raval, Ravi M.; Kulkarni, Abhishek A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Considering higher rate of postoperative wound complications in Government set up hospitals, this study was an attempt to compare incision time, incisional blood loss, hospital stay, post-operative pain and postoperative wound complications when subcutaneous tissue is opened with either scalpel or electrocautery in elective gynaecological surgeries after keeping all other clinical and surgical variables same i.e. age, BMI, haemoglobin, incision depth and hospital stay. Methods: This was a prospective observational comparative study conducted in one of the tertiary teaching hospital in Western Maharashtra, India over 12 months. All patients (n=100) were divided into 2 groups. Group A in which skin and subcutaneous tissue was dissected by using scalpel and Group B in which after skin, anterior abdominal wall was opened by using electrocautery. Data analyzed for indication, incisional blood loss, incision time, postoperative pain, wound complications and hospital stay. Results: There were no significant association between preoperative diagnosis and the development of a post-operative wound complications. Mean incision blood loss was found to be significantly higher in group A compared to group B patients. Postoperative pain was significantly higher in group A (P value <0.05). Among wound complications, no statistically significant differences were seen regarding wound complications for the two groups. Conclusions: Electrosurgical dissection for abdominal incision is safe, less time consuming and with less blood loss during subcutaneous incision and produces less postoperative pain. We conclude that the method of subcutaneous tissue incision was unrelated to the development of postoperative abdominal incision problems.